Makna Lakon Antasena Lahir - WAHYUDI, Aris
Antasena is Bima's son from mother Dewi Urangayu. He Was Unique character in Ngayogyakarta wayang world. As a Pandawa Knight, antasena was a powerful, wisdom, low-profile but unique knight. He's odd behavior against his other brother's. He never said politerly with everyone, just like Bima, his father.Antasena was the specific character in Ngayogyakarta wayang tradition, bacause it will not be found in Mahabharata tradition or other wayang traditions. His existence comes with his character, history, and life from born to die in wayang world. As Culture, Antasena was absolutely for place an idea.Through wayang mythology closing a mean in antasena character from his coming aspect was identification form ocean as javaneses explanation about ' jembar tanpa pagut' concept, a soul quality which must be built by javaneses to face a life. Thought analogy relation, we got that Indonesias real life (especially javaneses) should understand themselves to place it.